Mixed traditions: Evaluating telecommunications transparency - Ben Ballard; Christopher Parsons (Internet Policy Review, 2021)
This article draws upon academic and civil society literatures to create a framework for assessing the effectiveness of telecommunications transparency reports on government requests for information within Canada, the United Kingdom, and the United States. Our analysis suggests that effective reports are targeted, in that they embody both verifiable and performative approaches to transparency, and also are sustainable, insofar as they evolve in their scope and structure while remaining regularly published. Emergent from this evaluation, we can better explain why different companies, in different jurisdictions, demonstrate variation in their adoption of effective transparency reporting practices over the last decade.
Keywords: 300; Standards; Transparency; Telecommunication